Ta'widh Fee at BSI: A Review of the Shafi'i Mazhab and DSN-MUI Fatwa No. 43 of 2004 - Hidayat Hidayat (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Abstract: This study discusses the application of the ta'widh fee on the Hasanah Card product owned by Bank Syariah Indonesia (BSI), which is imposed on customers who are late in paying bills. In practice, this ta'widh fee resembles late fees in conventional banks, which are based on the concept of time value of money. This concept in the Islamic view includes usury, which is strictly prohibited. This research uses a library research method with a focus on the perspective of the Syafi'iyah Mazhab and the National Sharia Council Fatwa No. 43/DSN-MUI/VIII/2004. The results showed that according to the Shafi'i Mazhab, the imposition of late fines in the form of nominal money is haram, because it is a form of taking other people's property illegally. During the time of the Prophet, sanctions for lateness were more social or moral, not financial. This finding shows the difference in approach between contemporary fatwas and classical views in the application of sanctions for late payment.